2016
DOI: 10.1038/cddis.2016.135
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic CD8 T-lymphocytes disable macrophage-mediated immunity to Trypanosoma cruzi infection

Abstract: Chagas disease is caused by infection with the protozoan Trypanosoma cruzi. CD8 T-lymphocytes help to control infection, but apoptosis of CD8 T cells disrupts immunity and efferocytosis can enhance parasite infection within macrophages. Here, we investigate how apoptosis of activated CD8 T cells affects M1 and M2 macrophage phenotypes. First, we found that CD8 T-lymphocytes and inflammatory monocytes/macrophages infiltrate peritoneum during acute T. cruzi infection. We show that treatment with anti-Fas ligand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 56 publications
3
31
0
1
Order By: Relevance
“…We found that neutrophils exposed to both isolates display higher percentage of apoptosis compared with non-infected ones. Interestingly, Freire-de-Lima and colleagues demonstrated that macrophages in contact with apoptotic cells favor the intracellular parasite growth and increase parasitemia [ 44 , 45 ]. More recently, it was demonstrated that apoptotic neutrophils increase T .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that neutrophils exposed to both isolates display higher percentage of apoptosis compared with non-infected ones. Interestingly, Freire-de-Lima and colleagues demonstrated that macrophages in contact with apoptotic cells favor the intracellular parasite growth and increase parasitemia [ 44 , 45 ]. More recently, it was demonstrated that apoptotic neutrophils increase T .…”
Section: Discussionmentioning
confidence: 99%
“…cruzi replication in macrophages. They also showed that blocking apoptosis through anti-FasL treatment can restrict parasite growth and increase NO production [ 45 ]. Our analysis also showed that the higher the intensity of CFSE expression, indicating interaction with a higher number of parasites, the higher the expression of cytokines and the occurrence of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse experiments support the concept that phagocyte uptake of apoptotic T lymphocytes results in the establishment of an anti-inflammatory response dictated by TGF-β and prostaglandin PGE2 that fuels parasite persistence and disease ( 126 ). Treatment of T. cruzi infected mice with inhibitors of apoptosis reversed the anti-inflammatory phenotype and reduced ex vivo parasite replication ( 123 , 127 ), consistent with efferocytosis of apoptotic cells reducing macrophage anti-parasite activity and enhancing parasite persistence and disease.…”
Section: Efferocytosis In Pathogen Control and Its Subversion By Pathmentioning
confidence: 62%
“…Trypanosma cruzi infection induces lymphocyte apoptosis in both experimentally infected mice ( 122 , 123 ) and infected humans ( 124 ), and disease severity correlated with the degree of ex vivo apoptosis observed ( 124 , 125 ). Mouse experiments support the concept that phagocyte uptake of apoptotic T lymphocytes results in the establishment of an anti-inflammatory response dictated by TGF-β and prostaglandin PGE2 that fuels parasite persistence and disease ( 126 ).…”
Section: Efferocytosis In Pathogen Control and Its Subversion By Pathmentioning
confidence: 98%
“…TGF-β promotes in macrophages the L -arginine metabolism by arginase to synthesize polyamines which functions as a growth factor for parasites ( 66 ). Another work found that blocking apoptosis of CD8 + T cells in cocultures, infected macrophages increase NO levels and M1 features leading to restrict intracellular parasite growth ( 67 ). In addition, while coculture of apoptotic neutrophils induce an M2-like phenotype in infected macrophages, live neutrophils via elastase induce M1 macrophages with NO and TNF production that allow to control T. cruzi replication ( 68 ).…”
Section: Relevance To Cardiovascular Pathologiesmentioning
confidence: 99%